Students' Mathematical Conceptual Understanding Ability with Problem Posing Model on the Topic of Probability to Students' Curiosity Perspective - Hopiyeh, Hopiyeh; Husna, Nurul; Nurhayati, Nurhayati (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
Understanding concepts is crucial in facilitating students' learning to achieve mathematical goals. Strong and meaningful understanding serves as a vital foundation for problem-solving in daily life. However, In the fact, students' abilities in understanding concepts are still inadequate. Literature indicates that the problem posing learning model is effective in enhancing students' problem-solving abilities in mathematical learning. This study aims to determine the improvement of students' mathematical concept understanding abilities on probability material, considering students' curiosity before and after the implementation of the Problem Posing learning model. This research used a mixed-method approach with a Sequential Explanatory Design comprising 8 research stages. Quantitative research utilized Quasi Experimental Design with class VIIIB as the experimental group and class VIIIC as the control group. This research was conducted at SMP 20 Singkawang. Meanwhile, qualitative data analysis involves questionnaire categorization. The research findings reveal that: 1) There is a difference in the improvement of students' mathematical concept understanding abilities using the problem posing model, with an average score of 24.44 and a Z-score < Z-table. 2) The concept understanding abilities in terms of curiosity indicate an average score of 79.48, categorized as moderate.